In situ growth of Ag nanoparticles on α-Ag2WO4 under electron irradiation: Probing the physical principles - San-Miguel, Miguel A; Da Silva, Edison Z; Zanetti, Sonia M [UNESP]; Cilense, Mario [UNESP]; Fabbro, Maria T; Gracia, Lourdes; Andrés, Juan; Longo, Elson [UNESP] (IOP Publishing, 2016)
Exploiting the plasmonic behavior of Ag nanoparticles grown on α-Ag2WO4 is a widely employed strategy to produce efficient photocatalysts, ozone sensors, and bactericides. However, a description of the atomic and electronic structure of the semiconductor sites irradiated by electrons is still not available. Such a description is of great importance to understand the mechanisms underlying these physical processes and to improve the design of silver nanoparticles to enhance their activities. Motivated by this, we studied the growth of silver nanoparticles to investigate this novel class of phenomena using both transmission electron microscopy and field emission scanning electron microscopy. A theoretical framework based on density functional theory calculations (DFT), together with experimental analysis and measurements, were developed to examine the changes in the local geometrical and electronic structure of the materials. The physical principles for the formation of Ag nanoparticles on α-Ag2WO4 by electron beam irradiation are described. Quantum mechanical calculations based on DFT show that the (001) of α-Ag2WO4 displays Ag atoms with different coordination numbers. Some of them are able to diffuse out of the surface with a very low energy barrier (less than 0.1 eV), thus, initiating the growth of metallic Ag nanostructures and leaving Ag vacancies in the bulk material. These processes increase the structural disorder of α-Ag2WO4 as well as its electrical resistance as observed in the experimental measurements.
Keywords: Ag nanoparticles; density functional theory; plasmonic effect; transmission electron microscopy; α-Ag2WO4